2020
DOI: 10.1055/s-0040-1710521
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Surgical Technique and Tunnel Target Points and Placement in Anatomical Single-Bundle ACL Reconstruction

Abstract: The purpose of this systematic review was to reveal the trend in surgical technique and tunnel targets points and placement in anatomical single-bundle anterior cruciate ligament (ACL) reconstruction. Following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement, data collection was performed. PubMed, EMBASE, and Cochran Review were searched using the terms “anterior cruciate ligament reconstruction,” “anatomic or anatomical,” and “single bundle.” Studies were included whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…The 5th and 95th percentiles were 28% and 43%, respectively, for HL, and 24% and 37%, respectively, for DS. Iriuchishima et al[ 13 ] did a systematic study on the performed methods and tunnel placement strategies in anatomical single-bundle ACL reconstruction. Evaluation of 19 studies showed a targeted femoral footprint center at 32.3 ± 7% HL and at 30.6 ± 4.3% DS.…”
Section: Discussionmentioning
confidence: 99%
“…The 5th and 95th percentiles were 28% and 43%, respectively, for HL, and 24% and 37%, respectively, for DS. Iriuchishima et al[ 13 ] did a systematic study on the performed methods and tunnel placement strategies in anatomical single-bundle ACL reconstruction. Evaluation of 19 studies showed a targeted femoral footprint center at 32.3 ± 7% HL and at 30.6 ± 4.3% DS.…”
Section: Discussionmentioning
confidence: 99%
“…TP technique is a popular and widely practiced technique of ACLR, as it allows independent femoral tunnel drilling [ 9 , 10 ]. Among the advantages of this technique is it does not require special equipment, performance ease, and its ability to reach the center of the native ACL footprint [ 11 ]. However, a caveat to this technique is that it may result in disproportionate stress on the graft which increases the possibility of graft failure, rupture of the femoral posterior wall, and short femoral tunnel length [ 10 , 12 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The surgeon creates a tunnel by drilling in the direction guided by the instrument, and the operator can adjust the tunnel entry position at the lateral epicondyle. Therefore, many studies have been conducted on the effect of tunnel position on surgical outcome, and the femoral tunnel position is an important parameter when planning ACLR to restore knee stability [ 8 ]. Also, the femoral tunnel position has been reported to influence biomechanical characteristics of an implanted graft, and it affects knee function during postoperative rehabilitation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%